2011
DOI: 10.1042/bj20101904
|View full text |Cite
|
Sign up to set email alerts
|

OAT2 catalyses efflux of glutamate and uptake of orotic acid

Abstract: OAT (organic anion transporter) 2 [human gene symbol SLC22A7 (SLC is solute carrier)] is a member of the SLC22 family of transport proteins. In the rat, the principal site of expression of OAT2 is the sinusoidal membrane domain of hepatocytes. The particular physiological function of OAT2 in liver has been unresolved so far. In the present paper, we have used the strategy of LC (liquid chromatography)-MS difference shading to search for specific and cross-species substrates of OAT2. Heterologous expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 42 publications
1
53
1
Order By: Relevance
“…In cloning OAT2 from a human kidney cDNA library, we obtained variant 1 (OAT2-546aa). This variant was stably expressed in HEK cells and supported robust cGMP transport, as had been reported previously (Cropp et al, 2008;Fork et al, 2011). In addition to cGMP, OAT2-546aa was previously found to transport a number of other guanine-containing compounds, including guanine itself, 2Ј-deoxyguanosine, guanosine monophosphate, guanosine diphosphate, and guanosine triphosphate (Cropp et al, 2008).…”
Section: Oat2 In Kidney and Its Interaction With Select Antiviralssupporting
confidence: 74%
See 1 more Smart Citation
“…In cloning OAT2 from a human kidney cDNA library, we obtained variant 1 (OAT2-546aa). This variant was stably expressed in HEK cells and supported robust cGMP transport, as had been reported previously (Cropp et al, 2008;Fork et al, 2011). In addition to cGMP, OAT2-546aa was previously found to transport a number of other guanine-containing compounds, including guanine itself, 2Ј-deoxyguanosine, guanosine monophosphate, guanosine diphosphate, and guanosine triphosphate (Cropp et al, 2008).…”
Section: Oat2 In Kidney and Its Interaction With Select Antiviralssupporting
confidence: 74%
“…Although members of the OAT family are most known for their ability to interact with relatively small organic anions (Ͻ500 g/mol), acyclovir, ganciclovir, and penciclovir (225-250 g/mol) are neutral at physiological pH. Most recently, Fork et al (2011) showed that OAT2-546aa transports trigonelline, which is a small (137 g/mol) zwitterion. Together, these data indicate that the substrate specificity of OAT2-546aa is not restricted to compounds containing an anionic moiety but instead is relatively broad, as is the case with other drug transporters in the solute carrier family.…”
Section: Oat2 In Kidney and Its Interaction With Select Antiviralsmentioning
confidence: 99%
“…Because orotic acid transport proteins have only been identified in bacteria (Defoor et al, 2007), OAT2 is one of few organic anion transporters that has been shown to carry out this function in mammals. As discussed by the authors, orotic acid is not retained in the cells, but rather, efficiently eliminated by the kidney; thus, it may seem that hepatic uptake of orotic acid by OAT2 is not imperative (Fork et al, 2011). However, OAT2 may play an important role in orotic aciduria, a disease state associated with excessive urinary excretion of orotic acid, by facilitating the transport of large stores of orotic acid from hepatocytes.…”
Section: Organic Anion Transportersmentioning
confidence: 97%
“…Furthermore, Kobayashi et al (2005) proposed that the 4-carbon dicarboxylates, succinate and fumarate, are transported by OAT2 and are also capable of trans-stimulating the uptake of estronesulfate, which was recently, however, questioned by Rizwan and . Fork et al (2011) studied the substrate specificity of this transporter again to clarify the confusion over its precise mechanism of transport. Their studies involved the use of human embryonic kidney (HEK) 293 cells, which may be a more reliable expression system than X. laevis oocytes.…”
Section: Organic Anion Transportersmentioning
confidence: 99%
See 1 more Smart Citation